2023
DOI: 10.3389/fmicb.2023.1286187
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory mechanism of quercetin on Alicyclobacillus acidoterrestris

Xinhong Liang,
Cunjian Tu,
Yongchao Li
et al.

Abstract: In this the antibacterial of quercetin against Alicyclobacillus acidoterrestris was evaluated by measuring the minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC). Subsequently, the effect of quercetin on A. acidoterrestris cell membrane was evaluated through scanning electron microscopy (SEM), surface hydrophobicity determination, diacetate fluorescein staining and propidium iodide (PI) staining. Additionally, the effects of quercetin on intracellular macromolecules and cell me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Numerous researchers have investigated quercetin's antibacterial properties in depth and have looked into it as a potential treatment for a variety of oral pathogens. Recent investigations have shown that quercetin can disrupt the integrity of the bacterial cell membrane, thereby inhibiting bacterial growth [14,15]. Additionally, the cariogenic strains of Lactobacillus acidophilus (L. acidophilus) and Streptococcus mutans (S. mutans) prevented from proliferating the vesicles made with the highest concentration of mint oil.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous researchers have investigated quercetin's antibacterial properties in depth and have looked into it as a potential treatment for a variety of oral pathogens. Recent investigations have shown that quercetin can disrupt the integrity of the bacterial cell membrane, thereby inhibiting bacterial growth [14,15]. Additionally, the cariogenic strains of Lactobacillus acidophilus (L. acidophilus) and Streptococcus mutans (S. mutans) prevented from proliferating the vesicles made with the highest concentration of mint oil.…”
Section: Introductionmentioning
confidence: 99%